Chemical angioplasty with spasmolytics for vasospasm after subarachnoid hemorrhage - Hejčl, Aleš; Cihlář, Filip; Smolka, Vojtěch; Vachata, Petr; Bartoš, Robert; Procházka, Jan; Cihlář, Jiří; Sameš, Martin (Acta neurochirurgica, 2017)
BACKGROUND: Clinically symptomatic vasospasm leading to delayed ischemic neurological deficits occurs in up to 30% of patients with subarachnoid hemorrhage (SAH). Vasospasm can result in a serious decline in clinical conditions of patients with SAH, yet the algorithm for vasospasm treatment and prevention remains unclear. Intra-arterial administration of vasodilators is one of the modalities used for vasospasm therapy. METHODS: Over the last 7 years, we have treated 27 female and 7 male patients with vasospasm using intra-arterial administration of either nimodipine or milrinone; all had suffered aneurysm rupture. Of these patients, 28 were treated surgically (clip), and 6 patients had their aneurysm coiled. Spasmolytics were applied from day 2 to day 18 after rupture. RESULTS: Of the 53 procedures, angiographic improvement was documented in 92% of cases with a mean flow velocity decrease of 65 cm/s. Brain metabolism changes were monitored after the procedure. The highest level of immediate clinical improvement was observed in conscious patients with a focal neurological deficit (aphasia, hemiparesis). Overall clinical outcomes (Glasgow outcome scale, GOS) were as follows: GOS 5 (12 patients), GOS 4 (5 patients), GOS 3 (5 patients), GOS 2 (6 patients), and GOS 1 (6 patients). CONCLUSIONS: Intra-arterial administration of spasmolytics is a safe and potent method of vasospasm treatment. It is most effective when applied to conscious patients with a focal deficit. For unconscious patients, its therapeutic benefits are inconclusive. Patients in severe clinical states would further require use of other diagnostic tools such as multimodal brain monitoring to complement vasospasm therapy.
Keywords: Male; Cerebral vasospasm; lidé středního věku; Nimodipine; Vasospasm, Intracranial; Milrinone; subarachnoidální krvácení; Humans; intraarteriální infuze; Middle Aged; mužské pohlaví; Female; Subarachnoid Hemorrhage; Transcranial dopplerometry; angioplastika; Outcome; nimodipin; Spasmolytics; vazodilatancia; ženské pohlaví; Microdialysis; Angioplasty; Adult; intrakraniální vazospazmus; Infusions, Intra-Arterial; Angiography; dospělí; lidé; Vasodilator Agents